The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.vph.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid stabilizes cytoskeletal proteins and prevents TNF-α-induced disorganization of cell-cell junctions in human aortic endothelial cells

Abstract: Endothelial hyperpermeability represents an initiating step in early atherosclerosis and it often occurs as a result of endothelial barrier dysfunction. Asiatic acid, a major triterpene isolated from Centella asiatica (L.) Urban, has previously been demonstrated to protect against tumor necrosis factor (TNF)-α-induced endothelial barrier dysfunction. The present study aimed to investigate the mechanisms underlying the barrier protective effect of asiatic acid in human aortic endothelial cells (HAECs). The loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…A cell experiment found that asiatic acid reduced atherosclerosis by inhibiting the redistribution of occludin and zona occludens -1 (ZO-1). Furthermore, it decreased F-actin rearrangement and myosin light chain (MLC)dephosphorylation (Fong et al, 2019). Clinical studies have shown that after 4 years of intervention in patients with Pycnogenol ® 100 mg/day plus C. asiatica (100 mg/ day), the combined treatment group has reduced plaque progression, reduced oxidative stress, and mild transient brain deficiency as compared to the control group.…”
Section: Effects On Cardiovascular Diseasesmentioning
confidence: 99%
“…A cell experiment found that asiatic acid reduced atherosclerosis by inhibiting the redistribution of occludin and zona occludens -1 (ZO-1). Furthermore, it decreased F-actin rearrangement and myosin light chain (MLC)dephosphorylation (Fong et al, 2019). Clinical studies have shown that after 4 years of intervention in patients with Pycnogenol ® 100 mg/day plus C. asiatica (100 mg/ day), the combined treatment group has reduced plaque progression, reduced oxidative stress, and mild transient brain deficiency as compared to the control group.…”
Section: Effects On Cardiovascular Diseasesmentioning
confidence: 99%
“…In another study, the major compound of VE, quercetin 3-glucuronide, was shown to inhibit ROS generation and lipid peroxidation by increasing the activities of antioxidant enzymes, such as SOD and CAT, by upregulating heme oxygenase-1 via the transcription factors nuclear factor E2-related factor 2 and activator protein-1 ( Lee et al, 2017 ). In the case of C. asiatica , the major active compounds asiaticoside and asiatic acid protect against TNF-a-induced endothelial barrier dysfunction by abrogating the structural reorganization of occludin, ZO- 1, and adherens junction proteins, such as VE-cadherin and β-catenin ( Fong et al, 2015 ; Fong et al, 2019 ). Furthermore, madecassoside, another active constituent, inhibits p38 MAPK activity induced by H 2 O 2 in HUVECs ( Bian et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immunofluorescence staining of filamentous actin (F-actin) was conducted according to the methods reported previously [15]. Briefly, HUVECs were cultured on fibronectin-coated round coverslips at 1.5 × 10 5 cells/well for 4 d at 37°C to reach confluence.…”
Section: Methodsmentioning
confidence: 99%